2019
DOI: 10.1111/cpr.12628
|View full text |Cite
|
Sign up to set email alerts
|

DANCR promotes HCC progression and regulates EMT by sponging miR‐27a‐3p via ROCK1/LIMK1/COFILIN1 pathway

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited. AbstractObjectives: This research aims to verify that the long non-coding RNA differentiation antagonizing nonprotein coding RNA (LncRNA DANCR) could modulate the proliferation and metastasis of hepatocellular carcinoma (HCC), and it thus may work as a novel biomarker to render new orientation for early diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(48 citation statements)
references
References 30 publications
1
46
0
1
Order By: Relevance
“…Mechanistically, lncRNAs have been reported to regulate gene expression by interacting with proteins or miRNAs. 14,23 Large amounts of studies support that lncRNAs are competing endogenous RNAs (ceRNAs) for miRNAs in tumor. 9,20,21 For example, lncRNA KCNQ1OT1 promotes colon cancer chemoresistance through sponging miR-34a and upregulating ATG4B.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistically, lncRNAs have been reported to regulate gene expression by interacting with proteins or miRNAs. 14,23 Large amounts of studies support that lncRNAs are competing endogenous RNAs (ceRNAs) for miRNAs in tumor. 9,20,21 For example, lncRNA KCNQ1OT1 promotes colon cancer chemoresistance through sponging miR-34a and upregulating ATG4B.…”
Section: Discussionmentioning
confidence: 99%
“…DANCR could contribute to hepatocellular carcinoma malignancy via sponging miR-216a-5p and modulating KLF12 17 . In addition, Guo et al reported that DANCR could decoy miR-27a-3p to regulate ROCK1/LIMK1/COFILIN1 pathway to promote hepatocellular carcinoma progression 18 .…”
Section: Dancr In Various Cancersmentioning
confidence: 99%
“…Wang and Tao et al demonstrated that DANCR could directly interact with miR-216a-5p to regulate the expression of KLF12, Nanog, OCT4 and SOX2 17 , 32 . Guo et al found that DANCR could promote hepatocellular carcinoma development by decoying miR-27a-3p to regulate ROCK1/LIMK1/COFILIN pathway 18 . Wang et al revealed that DANCR could promote HSP27 expression and its mediation of proliferation/metastasis via miR-577 sponging in colorectal cancer 25 .…”
Section: Regulatory Mechanisms Of Dancr In Human Cancersmentioning
confidence: 99%
“…lncRNAs act as an endogenous molecular sponge, competitively binding miRNAs via shared miRNA response elements with reverse complementary binding seed regions, and thus indirectly regulating mRNA expression levels [15]. Many scientific studies have now confirmed the ceRNA hypothesis in hepatocellular carcinoma [16], breast cancer [17], and nonsmall cell lung cancer [18]. However, analyses of the CESC ceRNA network are rare and there is a lack of verification of the corresponding clinical data.…”
Section: Introductionmentioning
confidence: 99%